Penerapan Sensor Passive Infrared (Pir) Pada Pintu Otomatis Di Pt Zinus Dream Indonesia - Syehabudin, Syehabudin; Saputra, Rahmat (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2024)
A door is a medium that is used as a way to enter or exit a room. To make a job easier, an effective and efficient tool is needed. Conventional doors usually consist of a lock housing and a lock saddle to open them. Generally , in offices, doors can be made more practical. The door will automatically open if there is a stimulus (physical energy ) that moves it. For example, when someone wants to enter the room, the door will automatically open. Doors like this can be designed using automatic controls. This automatic door system can be designed using automatic control combined with sensors and motors. In terms of input equipment, a PIR (Passive Infrared) sensor is used that can detect the presence of a human approaching the door. This PIR sensor will send a signal to the control system unit . The controller will send the processing data to the motor so that it can open the door and close automatically. Keywords: Detection, Passive Infrared Sensor , Automatic Door